2012
DOI: 10.1021/jp301621y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Transport in Thin Thermoresponsive Poly(N-isopropylacrylamide) Brushes with Varying Grafting Density

Abstract: The effect of the grafting density on the molecular transport through thermoresponsive brushes of poly­(N-isopropylacrylamide) (PNIPAM) grafted onto flat gold substrates was investigated using voltammetry and impedance spectroscopy. PNIPAM brush layers were synthesized at four different grafting densities using surface-initiated atom transfer radical polymerization (SI-ATRP) from mixed self-assembled monolayers of ω-mercaptoundecyl bromoisobutyrate and undecanethiol chemisorbed on gold surfaces. Tethered PNIPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 22 publications
(51 reference statements)
3
21
1
Order By: Relevance
“…Regarding the diffusion of the K 3 [Fe(CN) 6 ]/K 4 [Fe(CN) 6 ] probe in neutral PNIPAM brushes, Gervasi et al observed a strong grafting density dependence: in the PNIPAM brushes of high grafting densities, the measured D of the redox probe was 7 orders of magnitude smaller than that in the bulk solution. Yet in the PNIPAM brushes of low grafting densities, the measured D was the same as that on the self‐assembled monolayer of initiators before brush synthesis . It seemed that the strong dependence of D on grafting density originated from the blocking effect of active sites on Au electrode surfaces for the impedance measurements.…”
Section: Diffusion Of Molecules Inside Polymer Brushesmentioning
confidence: 84%
“…Regarding the diffusion of the K 3 [Fe(CN) 6 ]/K 4 [Fe(CN) 6 ] probe in neutral PNIPAM brushes, Gervasi et al observed a strong grafting density dependence: in the PNIPAM brushes of high grafting densities, the measured D of the redox probe was 7 orders of magnitude smaller than that in the bulk solution. Yet in the PNIPAM brushes of low grafting densities, the measured D was the same as that on the self‐assembled monolayer of initiators before brush synthesis . It seemed that the strong dependence of D on grafting density originated from the blocking effect of active sites on Au electrode surfaces for the impedance measurements.…”
Section: Diffusion Of Molecules Inside Polymer Brushesmentioning
confidence: 84%
“…They observed that an increase in modulus was unambiguously correlated with a decrease in the permeability to iodide ion. 14 The same correlation was also observed in PNIPAM brushes 15 and hydrogels 16 ; a thermo-induced increase in stiffness or hydrophobicity was associated with a concomitant decrease in permeability. In principle, the permeability and mechanical properties of water-swollen systems such as polyelectrolyte multilayers, polymer brushes or hydrogels are expected to be strongly correlated because softer, more hydrated materials also tend to be more permeable.…”
Section: Introductionmentioning
confidence: 66%
“…Polymer brushes are assemblies of macromolecules that are tethered by one end to a surface. These macromolecular architectures bearing different functional groups along their backbones can be grafted on different surfaces, and even in constrained environments . There are two main strategies for generating polymer brushes on solid surfaces: “grafting to” and “grafting from.” In the “grafting‐to” technique, presynthesized polymers are anchored to a surface from solution.…”
Section: Functionalization Of Solid‐state Nanoporesmentioning
confidence: 99%